Shaping the regional structure in the modern Russian Federation - A. Z. Sapiev (Новые технологии, 2020)
The article considers shaping the regional structure in the modern Russian Federation. One of the vital functions of any state is the search for methods and forms of combining the interests of the state and its territories. The discrepancy between the interests of the state and its territorial entities, as well as the inhabitants of these territories, is a constant problem for any type of state. A state seeks to mitigate the high differentiation of its various territories, which is a destabilizing factor in the development of a state. Naturally, the difference between different regions is a consequence of the impact of natural and climatic conditions, socio-economic factors, as well as the peculiarities of the historical development of a particular region of a country. However, the state and the regions are concerned mainly due to the lagging behind a number of regions in socio-economic development. As a result, depressed regions appear. At present, in the Russian Federation there is a sharp differentiation due to the economic crisis and formation of new relations between the federal center and the regions. Taking into account the territorial extent of Russia, the achievement of sustainable development and stability is possible only with an even development of regions in economic and social terms. There is no progress on this issue on a national scale, because socio-economic and natural parameters of individual regions are worse than average ones in the state. For a modern state problems of sustainable development and territorial balance are especially important and should constantly be in the focus of the federal center.